Predation Pattern of the Asiatic Lion on Domestic Livestock - Singh, H. S.; Kamboj, R. D. (Indian Forester, 1996)
The predation pattern of Lion on domestic livestock in different seasons and regions of Gir Sanctuary have been studied. About 1,900 to 2,000 domestic livestock were killed by lions annual!y during recent past. Seasonal variations in the predation pattern has been recorded in which the maximum predation of domestic livestock by Lion in peripheral area has been noticed during the beginning of rainy season. It is observed that lions are more dependent on livestock hunting in Gir(E) as compared to Gir(W). High population density of domestic livestock creates negative impact on wild population of herbivores which also affect the predation pattern of the great cat. A Lion in Gir, on an average, kills 8 to 9 livestock mainly buffaloes and cows annually ascertaining the fact that â…“ of the Lions’ food is still constituted by the domestic livestock. Management prescriptions have been suggested to improve the habitat in some part of Gir in the benefits of herbivores to alter the livestock predation pattern of Lion in favour of wild ungulates.